Synthesis and Analgesic Activity of Some New Phenyl Sulfonyl Derivatives - Gupta, SUMIT; N. PANDEYA, SURENDRA; KUMAR, PRAVEEN; TRIPATHI, LAXMI (Asian Journal of Chemistry, 2010)
(±) Menthol (1) was oxidized to menthone (2) which was reacted with hydroxyl amine hydrochloride to yield menthone oxime (3). Menthone oxime (3) was converted to (2s,5r)-(±)-2-isopropyl-5-methyl-1-azacycloheptan-7-one (4) via Schmidt reaction, which was reacted with various substituted phenyl sulfonyl chlorides in alkaline medium to yield 7-isopropyl-4-methyl-1-(substituted phenyl sulfonyl)azepan-2-one (5a-g). The structure of all synthesized compounds have been established by analytical and spectral methods. These compounds have also been screened for analgesic activity.